The Civil War : an illustrated history - Ward, Geoffrey C. (Knopf, 1990)
The complete text of the bestselling narrative history of the Civil War--based on the celebrated PBS television series. This non-illustrated edition interweaves the author's narrative with the voices of the men and women who lived through that cataclysmic trail of our nationhood, from Abraham Lincoln to ordinary foot soldiers. Includes essays by distinguished historians of the era.